Effects of water drinking on cardiovascular responses to supine exercise and on orthostatic hypotension after exercise in pure autonomic failure. Issue 10 (9th May 2008) - Humm, A M; Mason, L M; Mathias, C J
Abstract : Objective: Patients with pure autonomic failure (PAF) have an abnormal fall in blood pressure (BP) with supine exercise and exacerbation of orthostatic hypotension (OH) after exercise. This study assessed the pressor effect of water on the cardiovascular responses to supine exercise and on OH after exercise. Methods: 8 patients with PAF underwent a test protocol consisting of standing for 5 min, supine rest for 10 min, supine exercise by pedalling a cycle ergometer at workloads of 25, 50 and 75 W (each for 3 min), supine rest for 10 min and standing for 5 min. The test protocol was performed without water ingestion and on a separate occasion after 480 ml of distilled water immediately after pre-exercise standing. Beat to beat cardiovascular indices were measured with the Portapres II device with subsequent Modelflow analysis. Results: All patients had severe OH pre-exercise (BP fall systolic 65.0 (26.1) mm Hg, diastolic 22.7 (13.5) mm Hg), with prompt recovery of BP in the supine position. 5 min after water drinking, there was a significant rise in BP in the supine position. With exercise, there was a clear fall in BP (systolic 42.1 (24.4) mm Hg, diastolic 25.9 (10.0) mm Hg) with a modest rise in heart rate; this occurred even after water ingestion (BP fall systolic 49.8 (18.9) mm Hg, diastolic 26.0 (9.1) mm Hg). BP remained low after exercise but was significantly higher after water intake, resulting in better tolerance of post-exercise standing. Conclusions: Water drinking did not change the abnormal cardiovascular responses to supine exercise. However, water drinking improved orthostatic tolerance post-exercise.